HP08: Deep Brain Stimulation Evoked Potentials in Children with dystonia. (March 2022) - Mcclelland, V.; Valentin, A.; Foddai, E.; Denison, T.; Lin, J.P.
Abstract : Pallidal Deep Brain Stimulation (DBS) is an established therapy for dystonia. Stimulation parameters are currently determined empirically. Recording the cortical response to the pallidal stimulus, known as Deep Brain Stimulation Evoked Potentials (DBSEPs) could provide a more objective measure of optimal contact selection (Tisch et al, MovDisord 2008;23:265-73; Bhanpuri et al, BrainStim 2014;7:718-26). Methods: Fifteen children with dystonia participated (age 7-19years), all with bilateral pallidal DBS implanted at least 6 months previously. Scalp EEG (10-20 system) was sampled at 5KHz. Contacts from each stimulating electrode were tested separately, using 6Hz bipolar stimulation. Pairs of electrode contacts were tested sequentially using combinations of cathodal stimulation (2 volts) with an adjacent anode, and pulse width at the patient's therapeutic level. Each combination was recorded for 3 minutes, giving >1000 stimuli per contact pair. Therapeutic settings were restored on study completion. Offline, the DBS stimulus artefact was used to segment EEG data into epochs (10ms pre-stimulus, 150ms post-stimulus). After artefact rejection, 900-1100 epochs were averaged to obtain the DBSEP for each contact pair. Results: Clear DBSEPs were obtained in 12/15 patients on one or both sides, with peak latency of 20ms, and largest amplitude over the ipsilateral central/centro-parietal region, concordant with adult literature. In 3/15 patients no convincing DBSEP was obtained. Conclusion: To our knowledge this is the largest study of DBSEPs in dystonia and confirms the feasibility and tolerability of this technique in children. Future work will investigate potential clinical applications of DBSEPs to inform an individualised approach to DBS parameter selection.